Thousands of RAD-seq Loci Fully Resolve the Phylogeny of the Highly Disjunct Arctic-Alpine Genus Diapensia (Diapensiaceae). - Yan Hou; Michael D Nowak; Virginia Mirré; Charlotte S Bjorå; Christian Brochmann; Magnus Popp (PLoS ONE, 2015)
Restriction-site associated DNA sequencing (RAD-seq) has recently become an important method to generate genome-wide molecular data for species delimitation, phylogeography, and population genetic studies. However, very few empirical studies have so far tested its applicability in phylogenetic reconstruction. The alpine-arctic genus Diapensia was selected to study the origin of the disjunction between the Arctic and the Himalayan-Hengduan Mountains (HHM). However, a previous phylogenetic analysis based on one nuclear and four plastid DNA regions failed to resolve the oldest divergences in Diapensia as well as the relationship between the two HHM species. Here we reconstruct a fully resolved phylogeny of Diapensia and address the conflict between the currently accepted taxonomy and the gene trees in the HHM species using RAD-seq. Based on a data set containing 2,650 loci selected to maximize the number of parsimony informative sites and allowing for a high level of missing data (51%), the phylogeny of Diapensia was fully resolved and each of the four species was reciprocally monophyletic. Whereas the arctic D. lapponica was inferred as sister to the HHM clade in the previous study, the RAD-seq data resolved the two arctic species as sisters to the HHM clade. Similar relationships were inferred from a differently filtered data set with far fewer loci (114) and less missing data (21%), but with lower support and with one of the two HHM species as non-monophyletic. Bayesian concordance analysis and Patterson's D-statistic tests suggested that admixture has occurred between the two HHM species.